A New Conceptual Model for Understanding International Students’ College Needs - Alfattal, Eyad (Journal of International Students, 2016)
This study concerns the theory and practice of international marketing in higher education with the purpose of exploring a conceptual model for understanding international students’ needs in the context of a four-year college in the United States. A transcendental phenomenological design was employed to investigate the essence of international students’ needs within their study experiences and explore a conceptual model that can explain these needs. Qualitative data were collected from 12 undergraduate and graduate international students through semi-structured interviews. Using thematic analysis, findings expand typical marketing mix frameworks and advance an eight-dimensional international student needs model: Program, Place, Price, Promotion, Process, People, Physical Facility, and Peace.